QAS by region - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Service centres will be set up in about 30 countries over four years. If your country is not listed, write to the centre most convenient to you. They will try to help as circumstances allow. Failing that, write to CTA.Southern Africa(Angola,...